Prophage-Related Gene VpaChn25_0724 Contributes to Cell Membrane Integrity and Growth of Vibrio parahaemolyticus CHN25 - Yang, Lianzhi; Wang, Yaping; Yu, Pan; Ren, Shunlin; Zhu, Zhuoying; Jin, Yinzhe; Yan, Jizhou; Peng, Xu; Chen, Lanming (Frontiers in Cellular and Infection Microbiology, 2020)
Vibrio parahaemolyticus is a leading seafood-borne pathogen that can cause acute gastroenteritis and even death in humans. In aquatic ecosystems, phages constantly transform bacterial communities by horizontal gene transfer. Nevertheless, biological functions of prophage-related genes in V. parahaemolyticus remain to be fully unveiled. Herein, for the first time, we studied one such gene VpaChn25_0724 encoding an unknown hypothetical protein in V. parahaemolyticus CHN25. This gene deletion mutant ΔVpaChn25_0724 was constructed by homologous recombination, and its complementary mutant ΔVpaChn25_0724-com was also obtained. The ΔVpaChn25_0724 mutant exhibited a sever defect in growth and swimming motility particularly at lower temperatures. Biofilm formation and cytotoxicity capacity of V. parahaemolyticus CHN25 was significantly lowered in the absence of VpaChn25_0724. Comparative secretomic analysis revealed an increase in extracellular proteins of ΔVpaChn25_0724, which likely resulted from its damaged cell membrane. Comparison of transcriptome data showed twelve significantly altered metabolic pathways in ΔVpaChn25_0724, suggesting inactive transport and utilization of carbon sources, repressed energy production and membrane biogenesis in ΔVpaChn25_0724. Comparative transcriptomic analysis also revealed several remarkably down-regulated key regulators in bacterial gene regulatory networks linked to the observed phenotypic variations. Overall, the results here facilitate better understanding of biological significance of prophage-related genes remaining in V. parahaemolyticus.